2010
DOI: 10.1155/2010/705382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Weight and Socioeconomic Status on Children's Growth in Mashhad, Iran

Abstract: Background. Socioeconomic status and birth weight are prominent factors for future growing of children. Also Studies show that this criterion is associated with reduced cognitive outcomes, school achievement, and adult work capacity. So in this paper we determined the effects of some socio-economic statuses and birth weight on physical growth of children in Mashhad, Iran. Method and materials. This is a cross sectional study that determined effect of socio-economic status and birth weight on weight, heighting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…However, from 9-12 months non-LBW babies grow faster than LBW babies. This finding is consistent with some studies that have reported that infants with low birth weight put on weight more rapidly than infants who were heavier at birth and can risk overweight (Mihrshahi et al, 2011, Mohammadzadeh et al, 2010. At the same time, LBW infants at the age of 9-12 months were growing slower compared to children with normal weight at birth and this is equally supported by other studies which have earlier shown that LBW can have difficulties to achieve standard weight or length at 12 months (Hien and Ushijima, 2007, Motta et al, 2005).…”
Section: Association Between Lbw and Mean Lazsupporting
confidence: 92%
“…However, from 9-12 months non-LBW babies grow faster than LBW babies. This finding is consistent with some studies that have reported that infants with low birth weight put on weight more rapidly than infants who were heavier at birth and can risk overweight (Mihrshahi et al, 2011, Mohammadzadeh et al, 2010. At the same time, LBW infants at the age of 9-12 months were growing slower compared to children with normal weight at birth and this is equally supported by other studies which have earlier shown that LBW can have difficulties to achieve standard weight or length at 12 months (Hien and Ushijima, 2007, Motta et al, 2005).…”
Section: Association Between Lbw and Mean Lazsupporting
confidence: 92%
“…The way an infant is fed is influenced by various factors. [ 1 2 ] The growth, learning, and participation in and contribution to communities are better in well-nourished children. [ 3 ] Any nutritional deficiency during growth and development would have long-term adverse effect on humans' lives.…”
Section: Introductionmentioning
confidence: 99%
“…Later in life, the prevalence of overweight can be higher in children with LBW i.e. birth weight less than 2500 gram [ 14 ].…”
Section: Introductionmentioning
confidence: 99%